2014
DOI: 10.1016/j.eatbeh.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and metabolic syndrome in obese individuals with binge eating disorder

Abstract: Menopausal transition has been associated with emergence of metabolic abnormalities, which may increase risk for chronic medical conditions in women. This study compared metabolic function between premenopausal women (n = 152), postmenopausal women (n = 88), and men (n = 98) recruited for treatment studies for obesity co-occurring with binge eating disorder (BED), a high risk population for developing metabolic syndrome (MetS). Postmenopausal women were more likely than premenopausal women to show elevated tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The second study examined the possible role of menopause in the relationship between metabolic syndrome and binge eating disorder [57]. They studied 152 premenopausal women, 88 postmenopausal women, and 98 age-matched men from a treatment study sample.…”
Section: Sex Differences In the Relationship Between Binge Eating Andmentioning
confidence: 99%
“…The second study examined the possible role of menopause in the relationship between metabolic syndrome and binge eating disorder [57]. They studied 152 premenopausal women, 88 postmenopausal women, and 98 age-matched men from a treatment study sample.…”
Section: Sex Differences In the Relationship Between Binge Eating Andmentioning
confidence: 99%
“…In fact, a longitudinal study reported individuals who reported binge eating were at greater risk for newly diagnosed metabolic syndrome symptoms, compared with non-binge eaters (Hudson et al, 2010). Consequently, individuals with BED and excess weight have been underscored as a significant subgroup with increased risk for developing metabolic syndrome (Abraham, Massaro, Hoffmann, Yanovski, & Fox, 2014; Barnes et al, 2011; Blomquist et al, 2012; Hudson, Hiripi, Pope, & Kessler, 2007; Mitchell, 2015; Sheehan & Herman, 2015; Udo, McKee, White, Masheb, Barnes, & Grilo, 2014a; Udo, McKee, White, Masheb, Barnes, & Grilo, 2014b). It is critical, therefore, to examine these individuals, with excess weight, metabolic syndrome, and binge eating disorder, as they may be at extreme risk for harmful health-related consequences.…”
Section: 1 Introductionmentioning
confidence: 99%
“…In examining a large cohort in a Finnish sample, Reavurori et al compared patients that had been seen for eating disorders treatment ( n = 2,342) versus control participants ( n = 9,368), and found strong support for an association between type II diabetes and clinically significant binge eating. Udo et al in 2014 in studying 152 treatment‐seeking obese found that the development of the metabolic syndrome abnormalities seemed to be best explained by aging as the most powerful risk factor rather than menopause, while Adani et al, also in 2014, in studying obese adolescents including those with subclinical BED symptoms found no difference in serum glucose levels between those affected and those unaffected. Most recently, Çelik et al reported that among 152 patients age 18–75 with type II diabetes, those with versus those without BED evidenced no difference in HgA1c.…”
Section: Introductionmentioning
confidence: 99%